Faktor Eksternal dan Internal yang Mempengaruhi Profitabilitas Bank Syariah di Indonesia - Yudhistira Ardana (Cakrawala: Jurnal Studi Islam, 2018)
This study aims to determine the influence of external factors (inflation and BI rate) and internal (CAR, REO, FDR, and NPF) on the level of profitability of sharia banks in Indonesia as measured by ROA. The data used in this study is the data of Sharia Commercial Bank and Sharia Business Unit in Indonesia from 2011 to 2018 using monthly data. This research uses error correction model which is commonly abbreviated as ECM. The results show that the external and internal variables together significantly influence the ROA variable. Individually, CAR, NPF and Inflation variables have no significant effect on ROA, while FDR and REO variables in both short and long term have significant effect on ROA. BI rate in this study has no significant effect on ROA in the short term, but has a significant effect on ROA variable in the long term